2008
DOI: 10.1007/s00105-008-1591-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetische Ursachen schwerer Wundheilungsstörungen

Abstract: Chronic leg ulcers affect about 1% of the German population. The intense search for the underlying cause of impaired wound healing is an essential requirement for successful therapy. The most common causes comprise chronic venous insufficiency (70%), peripheral arterial occlusive disease (10%) and diabetes mellitus. Besides vasculitis, infectious diseases and tumors, genetic diseases may constitute the underlying cause for impaired wound healing. In this review various rare genetic diseases causing chronic wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
2
0
3
Order By: Relevance
“…55 However, unregulated healing processes, due to genetic or epigenetic factors, can lead to impairment in cellular function. 56 , 57 Macé et al 41 have shown antiproliferative and hyperapoptotic phenotype in KC-affected cornea, which also reveals a defect in wound healing process. Aquaporins (AQPs) are a ubiquitous family of transmembrane water channels to maintain tear film osmolarity, stromal layer thickness, and corneal transparency.…”
Section: Discussionmentioning
confidence: 99%
“…55 However, unregulated healing processes, due to genetic or epigenetic factors, can lead to impairment in cellular function. 56 , 57 Macé et al 41 have shown antiproliferative and hyperapoptotic phenotype in KC-affected cornea, which also reveals a defect in wound healing process. Aquaporins (AQPs) are a ubiquitous family of transmembrane water channels to maintain tear film osmolarity, stromal layer thickness, and corneal transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal wound healing is a complex process controlled by the integrated actions of multiple growth factors, cytokines, and proteases produced by epithelial cells, stromal keratocytes, and inflammatory cells 49 . However, unregulated healing processes, due to genetic or epigenetic factors, can lead to impairment in cellular function 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Von den zahlreichen potenziell mit dem Auftreten eines Ulcus cruris assoziierten genetischen Erkrankungen (16) (13). Somit kommt es gehäuft zu einem Ulcus cruris postthromboticum.…”
Section: Genetische Defekteunclassified